Surface Plasmon Resonance study of Ag nanoparticles colloidal - k. Mahmood, Waleed; k. Ibrahim, Rawa; N. Naje, Asama (Iraqi Journal of Science, 2021)
Silver nanoparticles (Ag-NPs) have been prepared using the electro-chemicalmethod. The experimental setup of this technique consist of two electrodes of puresilver (99.2 %), the applied voltage on the electrodes is 20 V and the current throughthe colloidal was about 0.4 Amp. The silver nanoparticles crystallization has beenstudied; the crystalline structure appears Face center Cubic. The optical properties ofsilver nanoparticles are strongly affected by the Local Surface Plasmon Resonance(LSPR). The wavelength of maximum absorption band for an Ag NPs have a range(~350nm-550nm).